Global comparison of hedge fund regulations - Stoll-Davey, C; Dr. Camille Stoll-Davey (2008)
The regulation of hedge funds has been at the centre of a global policy debate for much of the past decade. Several factors feature in this debate including the magnitude of current global investments in hedge funds and the potential of hedge funds to both generate wealth and destabilise financial markets. The first part of the thesis describes the nature of hedge funds and locates the work in relation to four elements in existing theory including regulatory competition theory, the concept of differential mobility as identified by Musgrave, Kane’s concept of the regulatory dialectic between regulators and regulatees, and the concept of unique sets of trust and confidence factors that individual jurisdictions convey to the market. It also identifies a series of questions that de-limit the scope of the present work. These include whether there is evidence that regulatory competition occurs in the context of the provision of domicile for hedge funds, what are the factors which account for the current global distribution of hedge fund domicile, what latitude for regulatory competition is available to jurisdictions competing to provide the domicile for hedge funds, how is such latitude shaped by factors intrinsic and extrinsic to the competing jurisdictions, and why do the more powerful onshore jurisdictions competing to provide the domicile for hedge funds not shut down their smaller and weaker competitors? The second part of the thesis examines the regulatory environment for hedge funds in three so-called offshore jurisdictions, specifically the Cayman Islands, Bermuda and the British Virgin Islands, as well as two onshore jurisdictions, specifically the United Kingdom and the United States. The final section presents a series of conclusions and their implications for both regulatory competition theory and policy.